2016
DOI: 10.20944/preprints201611.0071.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Anti Diabetic Drugs on Lipid Profile in Patients with Type 2 Diabetes Mellitus

Abstract: Diabetes mellitus (DM) has been defined as a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. This study includes (84) subjects, their age ranged from (40 to 54) years. (20) subjects were healthy chosen as control group and (64) patients with type 2 diabetes mellitus were divided into three groups according to their type of anti diabetic therapy: (23) newly diagnosed group without therapy (Group1), (20) with metformin therapy (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…On the other hand , the current The current finding agreed with results previously reported by (32) the findings an increase in the levels of fasting blood glucose, HbA1C, cholesterol, triglycerides, LDL, as well as VLDL, but the levels of HDL was opposite to the current study which was decreased in patients with T2DM compared to control, some other studies also showed the HDL was increasing in T2DM (33).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand , the current The current finding agreed with results previously reported by (32) the findings an increase in the levels of fasting blood glucose, HbA1C, cholesterol, triglycerides, LDL, as well as VLDL, but the levels of HDL was opposite to the current study which was decreased in patients with T2DM compared to control, some other studies also showed the HDL was increasing in T2DM (33).…”
Section: Discussionsupporting
confidence: 92%
“…As well as the results agreed with (35)showed that mean cholesterol was found to be statistically significant (p<0.05) in Group 1 (newly diagnosed group) when compared with control groupin , (32)who found that patients with T2DM have significantly higher serum concentrations of cholesterol, also the results of HDL revealed that mean HDL-C was found to be significantly different (p<0.05) in diabetic patients compared with control group. Type 2 diabetes is characterized by low HDL cholesterol (HDL-C) and HDL dysfunction and results of LDL was found to be significantly different (p<0.05) when compared with control group.…”
Section: Discussionsupporting
confidence: 82%
“…GBE had also been reported to up-regulate a suite of genes related to peroxisomes and microsomes oxidation in an NAFLD rat model, such as straight-chain acyl-CoA oxidase (Acox), PPARα, and cytochrome P450 enzymes, indicators of fatty acid consumption. Quercetin and kaempferol were also confirmed to affect partial genes [23][24][25][26][27]. Therefore, GBE and its flavonoids might increase CPT1A expression to promote β-oxidation in mitochondria, as well as in peroxisomes and microsomes.…”
Section: Resultsmentioning
confidence: 99%
“…Several therapeutically interesting 1,2,3-triazoles have been reported, including anti-HIV agents [4], antimicrobial compounds [5], -selective adrenergic receptor agonists [6], kinase inhibitors [7] and other enzyme inhibitors [8]. The 1,2,3-triazole moiety is also present in a number of drugs, for example, the β-lactam antibiotic tazobactam [9] and the cephalosporin cefatrizine [10]. The presence of three nitrogen hetero-atoms in five-membered ring systems defines the triazole as an interesting class of compounds.…”
Section: Introductionmentioning
confidence: 99%